1993
DOI: 10.1093/milmed/158.7.474
|View full text |Cite
|
Sign up to set email alerts
|

A One-Year Look at the Impact of Cholesterol Screening, Education, and Counseling

Abstract: During 1989 and 1990, we offered cholesterol screening in conjunction with National Medical Laboratory Week. The proportions of subjects categorized as hypercholesterolemic decreased in 1990 in each eligibility category except family members. Active duty subjects decreased from 39% to 30%, retired subjects from 60% to 55%, and civilian subjects from 51% to 43%. These changes were also reflected in significant decreases in the mean cholesterol levels for retired and civilian subjects. The data suggest a downwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is interesting that Schmidt and Telch (1997)found that perceptions of good physical health were associated with lower levels of anxiety sensitivity. Although perceived physical health was not assessed in the present sample, comprehensive physical screening ensures higher than average levels of physical health (Bray, Marsden, & Peterson, 1991; Love & McBride, 1993), which, in turn, is highly associated with better perceived health (Schmidt & Telch, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…It is interesting that Schmidt and Telch (1997)found that perceptions of good physical health were associated with lower levels of anxiety sensitivity. Although perceived physical health was not assessed in the present sample, comprehensive physical screening ensures higher than average levels of physical health (Bray, Marsden, & Peterson, 1991; Love & McBride, 1993), which, in turn, is highly associated with better perceived health (Schmidt & Telch, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…Although perceived physical health was not assessed in the present sample, comprehensive physical screening ensures higher than average levels of physical health (Bray, Marsden, & Peterson, 1991;Love & McBride, 1993) which, in turn, is highly associated with better perceived health (Schmidt & Telch, in press).…”
Section: Discussionmentioning
confidence: 99%